Periodontal conditions of teeth presenting pathologic migration Condições periodontais de dentes com migração dentária patológica - Maurício Ribeiro Costa; Karina Gonzales Silvério; Carlos Rossa Júnior; Joni Augusto Cirelli (Sociedade Brasileira de Pesquisa Odontológica, 2004)
The aim of the present study was to evaluate the periodontal conditions of anterior teeth that presented pathologic migration in patients with chronic periodontitis and to compare periodontal destruction in migrated versus non-migrated teeth. The sample included 32 patients of both sexes (mean age: 46.0 ± 11.6 years) diagnosed with generalized chronic periodontitis and selected on the basis of the presence of pathologic migration in one or more anterior teeth. This migration was classified according to the following categories: facial flaring, diastema, proximal tilting, rotation or extrusion. The periodontal parameters recorded were clinical attachment loss (CAL) and percentage of radiographic bone loss (BL). Mean CAL of 5.50 ± 2.20 mm and mean BL of 41.90 ± 15.40% were found in 115 teeth assessed. The most frequent type of migration was facial flaring (34.80%), followed by diastema (27.00%). Extrusion was hardly observed in the sample (4.30%). However, greater severity of BL and CAL were observed in teeth with this type of migration (59.44% and 8.42 mm, respectively), and in teeth with facial flaring (45.17% of BL and 6.07 mm of CAL). Kruskal-Wallis test indicated that BL presented by teeth with extrusion or facial flaring was greater than that observed in rotated or tilted teeth (p < 0.05), while there was no difference between groups regarding CAL (p = 0.11). It was observed that anterior teeth with pathologic migration presented greater CAL and BL (5.1 mm and 40%) than non-migrated teeth (4.1 and 31%). The study indicated that the most prevalent kind of pathologic migration is facial flaring, which was associated to higher level of bone loss. O objetivo deste estudo foi avaliar as condições clínicas periodontais de dentes anteriores com migração patológica (MDP) em pacientes com periodontite crônica generalizada e comparar a severidade de destruição periodontal entre dentes migrados e não-migrados. Foram selecionados 32 pacientes, de ambos os sexos, apresentando média de idade de 46,0 anos (± 11,6), com perda clínica de inserção em dentes anteriores e presença de algum tipo de MDP, a saber: vestibularização, diastema, inclinação proximal, giroversão ou extrusão. Os parâmetros avaliados foram a perda clínica de inserção (PIC) e o percentual de perda óssea radiográfica (PO). Os resultados mostraram, em média, uma PIC de 5,50 mm (± 2,20 mm) e uma PO de 41,90% (± 15,40%) do comprimento radicular, em 115 dentes selecionados. Os tipos mais freqüentes de migração foram vestibularização (34,80%) e presença de diastemas (27,00%). A extrusão foi a menos freqüente (4,30%). Maiores valores de PO e PIC foram registrados nos dentes com extrusão (59,44% e 8,42 mm) e vestibularização (45,17% e 6,07 mm). Esses valores de PO foram superiores aos observados nos dentes com giroversão ou inclinação proximal (p < 0,05 - Kruskal-Wallis). A PIC não apresentou diferenças significativas entre os diferentes tipos de migração (p = 0,11). Constatou-se que os dentes anteriores com MDP apresentaram maior PIC e PO (5,1 mm e 40%) quando comparados aos não-migrados (4,1 mm e 31%). Pôde-se concluir também que o tipo de MDP mais prevalente foi a vestibularização, que esteve relacionada a maiores níveis de perda óssea.